2013
DOI: 10.1089/sur.2013.9999
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Practice Guidelines for Antimicrobial Prophylaxis in Surgery

Abstract: T hese guidelines were developed jointly by the American Society of Health-System Pharmacists (ASHP), the Infectious Diseases Society of America (IDSA), the Surgical Infection Society (SIS), and the Society for Healthcare Epidemiology of America (SHEA). This work represents an update to the previously published ASHP Therapeutic Guidelines on Antimicrobial Prophylaxis in Surgery [1], as well as guidelines from IDSA and SIS [2,3]. The guidelines are intended to provide practitioners with a standardized approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
1,286
5
77

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,202 publications
(1,388 citation statements)
references
References 968 publications
(1,671 reference statements)
20
1,286
5
77
Order By: Relevance
“…This approach is consistent with international consensus guidelines. 29 Risk-adjustment is necessary for reporting SSI surveillance data, 30 and we applied risk-indexing according to criteria established by the NHSN/CDC (Table 1). 17 These data confirm that crude SSI rates do not reliably reflect trends or enable interhospital comparison.…”
Section: Discussionmentioning
confidence: 99%
“…This approach is consistent with international consensus guidelines. 29 Risk-adjustment is necessary for reporting SSI surveillance data, 30 and we applied risk-indexing according to criteria established by the NHSN/CDC (Table 1). 17 These data confirm that crude SSI rates do not reliably reflect trends or enable interhospital comparison.…”
Section: Discussionmentioning
confidence: 99%
“…Single-dose antibiotic prophylaxis is part of routine patient care prior to surgery or admission into the ICU (55,(74)(75)(76)(77). Studies have shown that administering antibiotic prophylaxis reduces postsurgical infections by up to 50% (78) and is similarly effective in reducing ICU-acquired infections (79).…”
Section: Discussionmentioning
confidence: 99%
“…Because the risk of hospital-acquired infection increases as a result of surgery or prolonged stay (such as in intensive care units), patients generally receive prophylactic doses of antibiotics prior to undergoing any procedure (50)(51)(52)(53). Vancomycin is a broad-spectrum antibiotic that is sometimes given as prophylaxis before surgery (54,55). To assess whether the administration of vancomycin could effectively reduce the pathologies observed in animals exposed to propofol and infected with MRSA, mice were treated with vehicle alone, propofol alone, or vehicle or propofol plus a prophylactic single intravenous dose of vancomycin 24 h prior to tail vein infection with MRSA.…”
mentioning
confidence: 99%
“…Total pasien kanker payudara yang dilakukan kultur berjumlah 7 orang pasien, terdiri dari 3 orang pasien di [16,17,18].…”
Section: Hasil Dan Diskusiunclassified
“…Peresepan antibiotik profilaksis dilakukan secara empiris dan berdasarkan keahlian dokter penulis resep, dan menurut apoteker pemilihan antibiotik hanya merujuk kepada Formularium Nasional tahun 2016. Antibiotik yang digunakan sebagai antibiotik profilaksis operasi kanker payudara adalah sefazolin yang merupakan sefalosporin generasi I [16,29,31]. Sementara penggunaan antibiotik terbanyak pada pasien operasi kanker payudara adalah seftriakson sebesar 77,8% yang merupakan antibiotik golongan sefalosporin generasi III.…”
Section: G2unclassified